Propuesta arquitectónica de un centro geriátrico para el sector Mucho Lote 2 en la ciudad de Guayaquil - Oviedo Peñafiel, Gabriel Stalyn (2023)
The project deals with an architectural proposal for a geriatric center, located in Mucho Lote 2, Guayaquil City of Ecuador, this sector does not have a geriatric center for the proper care of the elderly, because of this drawback is proposed to design a geriatric center that has all the necessary equipment for the care of adults, according to INEN construction standards is required to obtain a comfortable and adequate space for users. Part of the process involved the use of surveys to the residents of the sector to find out what needs are present. The design of the geriatric center is focused on deconstructivist architecture, which is characterized by being an avant-garde movement that does not follow the rules and plays with different forms, but within the design it is characterized by having wide spaces free of obstacles, adequate lighting, the colors used are light tones to provide visual comfort and harmonious environment for adults.